2009
DOI: 10.1186/1471-2148-9-48
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthetase sequence evolution in the mycobacteria and their use as molecular markers for Actinobacteria speciation

Abstract: Background: Although the gene encoding for glutamine synthetase (glnA) is essential in several organisms, multiple glnA copies have been identified in bacterial genomes such as those of the phylum Actinobacteria, notably the mycobacterial species. Intriguingly, previous reports have shown that only one copy (glnA1) is essential for growth in M. tuberculosis, while the other copies (glnA2, glnA3 and glnA4) are not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…S2; ref. 23), and GlnR has been shown to regulate their expression (24). We found that two GS enzymes, GSI-β GlnA1 and GSII GlnA4, were directly acetylated in vitro after incubation with AcuA and AcCoA; AcuA did not acetylate GlnA2 or GlnA3 ( Fig.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…S2; ref. 23), and GlnR has been shown to regulate their expression (24). We found that two GS enzymes, GSI-β GlnA1 and GSII GlnA4, were directly acetylated in vitro after incubation with AcuA and AcCoA; AcuA did not acetylate GlnA2 or GlnA3 ( Fig.…”
Section: Resultsmentioning
confidence: 74%
“…GSI is largely absent in eukaryotes, but plays a vital role in many microorganisms, existing as α-and β-isoforms that differ in terms of sequence (35-41% identity), regulatory mechanisms (feedback allosteric regulation or adenylylation regulation), and biological functions (catalytic and chaperone activities) (28). Both the GSI-β and GSII enzymes are found in actinomycetes, and are distinguishable from each other by specific 25-amino acid insertion sequences (23). In this study, we found that AcuA-dependent lysine acetylation exerts different effects on four GS enzymes in S. erythraea: inactivation of one GSII enzyme (GlnA4) by acetylation, gain of chaperone activity of one GSI-β (GlnA1) by acetylation, and no acetylation of the other two GSII 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4N2-2 appears to belong to a family of highly conserved bacterial GSs (39). Other bacterial GSs that acetylate fluoroquinolones may also exist, considering that GS is conserved in actinobacteria with high structural homology (21,39) and that N-acetylation activity for norfloxacin is found in several Mycobacterium spp. (15).…”
Section: Discussionmentioning
confidence: 99%